Phylogenomic analysis of Wolbachia genomes from the Darwin Tree of Life biodiversity genomics project - Vancaester, Emmelien; Blaxter, Mark (PLOS Biology, 2023)
Wolbachia are common bacterial endosymbionts that manipulate reproductive biology in their hosts. This study assembles the genomes of 110 Wolbachia coincidentally sequenced alongside their insect hosts, finding a rich diversity of host manipulation loci.